Assisted dying for prison populations: Lessons from and for abroad. (June 2019) - Downie, Jocelyn; Iftene, Adelina; Steeves, Megan
Canadian federal legislation setting out the framework for medical assistance in dying (MAiD) in Canada came into effect in June 2016. Because of section 86(1) of the Corrections and Conditional Release Act, as soon as MAiD became available in the community, it also needed to be made available to federal prisoners. There are some good reasons to be concerned about MAiD in the Canadian corrections system based on logistical, legal, and moral considerations. Fortunately, Canada is not the first country to decriminalize assisted dying and so Canadian policies and practices can be compared to others and take some lessons from their experiences. Thus, by reviewing the legal status of assisted dying in prisons internationally, the regulation of assisted dying, demand for assisted dying from prisoners, and the process for prisoners accessing assisted dying, this article offers a comparative overview of assisted dying for prisoners around the world in an effort to inform Canadian and other jurisdictions' law, policy, and practice.